Augmentation of the pulmonary arteries at or prior to the Fontan procedure is not associated with worse long-term outcomes: a propensity-matched analysis from the Australia-New Zealand Fontan Registry. (27th November 2018) - Shearer, Lauren; Justo, Robert N; Marathe, Supreet P; Betts, Kim; Venugopal, Prem; Winlaw, David S; Bullock, Andrew; Robertson, Terry; Gentles, Thomas L; Celermajer, David; d'Udekem, Yves; Alphonso, Nelson
Abstract: OBJECTIVES: Long-term data on the impact of pulmonary artery (PA) augmentation in patients who underwent the Fontan procedure are lacking. The aim of this study was to examine whether surgical or transcatheter PA augmentation at or prior to the Fontan procedure adversely affects the outcomes. METHODS: Data of 1436 patients from the Australia-New Zealand Fontan Registry (1975–2015) were analysed. Primary end point was death or Fontan failure. Cox regression with propensity score matching was used to determine risk or benefit conferred by PA augmentation. RESULTS: Forty-eight (3.3%) patients underwent PA augmentation following cavopulmonary shunt (surgical n  = 14, balloon dilatation n  = 16 and stent n  = 18) and 105 (7.3%) patients underwent PA augmentation at the time of the Fontan procedure (surgical n  = 104, stent n  = 1). Median follow-up was 6.4 years with 10 deaths (6.5%) in the augmentation group and 10.5 years with 95 deaths (7.4%) in the non-augmentation group. The unadjusted Kaplan–Meier, log-rank test and Cox regression analysis demonstrated no significant difference in both end points between the 2 groups [death: hazard ratio (HR) 1.35, 95% confidence interval (CI) 0.70–2.60; P  = 0.37 death or failure: HR 1.39, 95% CI 0.83–2.34; P  = 0.21]. The propensity score matching yielded 131 matched pairs, with adequate balance for all covariates (the median residual bias = 0.05). The subsequent Cox regression demonstrated no significant difference in the risks of death (HR 1.30, 95% CI 0.49–3.41; P  = 0.60) and death or Fontan failure (HR 0.92, 95% CI 0.46–1.85; P  = 0.82). CONCLUSIONS: PA augmentation prior to or at the Fontan procedure does not confer worse long-term outcomes.